2017
DOI: 10.1111/crj.12660
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐lymphocyte ratio and a dosimetric factor for predicting symptomatic radiation pneumonitis in non‐small‐cell lung cancer patients treated with concurrent chemoradiotherapy

Abstract: The NLR at radiological RP is a useful biomarker for predicting symptomatic RP development after CCRT in stage III NSCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(57 reference statements)
0
16
0
Order By: Relevance
“…There are very few studies evaluating their role in stage I NSCLC undergoing SBRT [15], [16]. Most of these studies have limited their blood values measured within the 3 month period prior to initiating therapy [9], [10], [11], [12], [13], [15], [17]. Moreover, none of the studies have evaluated the changes in the values of the hematological parameters between pre-SBRT and post-SBRT.…”
Section: Introductionmentioning
confidence: 99%
“…There are very few studies evaluating their role in stage I NSCLC undergoing SBRT [15], [16]. Most of these studies have limited their blood values measured within the 3 month period prior to initiating therapy [9], [10], [11], [12], [13], [15], [17]. Moreover, none of the studies have evaluated the changes in the values of the hematological parameters between pre-SBRT and post-SBRT.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Current studies have shown that NLR can predict the occurrence of radiation pneumonia in patients with tumor radiotherapy. 17 , 18 Lee et al pointed out that NLR combined with dosimetric factors could predict symptomatic radiation pneumonitis in patients with NSCLC who received concurrent radiotherapy and chemotherapy. 17 Pan et al found that combining NLR, V20, and mean lung dose could predict radiation-induced lung injury in lung cancer patients receiving concurrent IMRT and chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 Lee et al pointed out that NLR combined with dosimetric factors could predict symptomatic radiation pneumonitis in patients with NSCLC who received concurrent radiotherapy and chemotherapy. 17 Pan et al found that combining NLR, V20, and mean lung dose could predict radiation-induced lung injury in lung cancer patients receiving concurrent IMRT and chemotherapy. 18 Multivariate analysis showed that total dose ≥60 Gy, V20 ≥20%, mean lung dose ≥12 Gy, and NLR ≥2.2 were still independent predictors of RP ( P =0.010, 0.043, 0.028, and 0.015, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite being treated according to the dose constraint guidelines for radiation treatment planning, patients still experience Gr ≥ 2 RP. It is believed that the underlying mechanism associated with the patient's robust immune reaction may be associated with this [4].…”
Section: Introductionmentioning
confidence: 99%